2022
DOI: 10.1177/13524585221102921
|View full text |Cite
|
Sign up to set email alerts
|

Paramagnetic rim lesions are associated with pathogenic CSF profiles and worse clinical status in multiple sclerosis: A retrospective cross-sectional study

Abstract: Background: Paramagnetic rims have been observed as a feature of some multiple sclerosis (MS) lesions on susceptibility-sensitive magnetic resonance imaging (MRI) and indicate compartmentalized inflammation. Objective: To investigate clinical, MRI, and intrathecal (cerebrospinal fluid, CSF) associations of paramagnetic rim lesions (PRLs) using 3T MRI in MS. Methods: This is a retrospective, cross-sectional analysis. All patients underwent 3T MRI using a T2*-weighted sequence with susceptibility postprocessing … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
2

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 41 publications
1
17
2
Order By: Relevance
“…A recent study also investigated the relationship between IRLs and clinical, MRI and CSF profiles. 18 Besides an association of IRLs with worse disease severity and lower brain volumes, the authors also found a pathologically elevated albumin quotient as a marker of blood–CSF barrier disruption in MS patients with IRLs. 18 We now provide some additional observations regarding the association between IRLs, pathogenic CSF profiles and a CSF-related tissue injury.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…A recent study also investigated the relationship between IRLs and clinical, MRI and CSF profiles. 18 Besides an association of IRLs with worse disease severity and lower brain volumes, the authors also found a pathologically elevated albumin quotient as a marker of blood–CSF barrier disruption in MS patients with IRLs. 18 We now provide some additional observations regarding the association between IRLs, pathogenic CSF profiles and a CSF-related tissue injury.…”
Section: Discussionmentioning
confidence: 88%
“…However, the average interval between CSF analysis and time point of MRI in this study was similar to that in a previous study. 18 Patients with acute relapses have higher CSF leukocyte counts than patients with chronic progressive or inactive disease, 29 and previous studies demonstrated that the CSF leukocyte count and the albumin CSF/serum quotient correlate with proximity of lesions to the lumbar CSF space and the temporal latency of the LP at the time of relapse. 30 , 31 While CSF leukocyte counts might decrease under DMTs, the humoral response (IgG synthesis) usually remains unchanged.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…35 However, most recently, elevated albumin quotient, a subtle biomarker of impaired BBB, has been detected in patients with PRLs, confirming that impaired BBB that leads to chronic inflammation is most probably insidious and omnipresent, yet invisible to the naked eye in terms of gadolinium enhancement. 36…”
Section: Discussionmentioning
confidence: 99%
“…35 However, most recently, elevated albumin quotient, a subtle biomarker of impaired BBB, has been detected in patients with PRLs, confirming that impaired BBB that leads to chronic inflammation is most probably insidious and omnipresent, yet invisible to the naked eye in terms of gadolinium enhancement. 36 Although the pathophysiology underlying GCIPL and pRNFL thinning is not entirely clear, the currently prevailing concept comprises retrograde degeneration secondary to axonal damage occurring at any point within the brain. 37 In previous studies, GCIPL thinning and to a lesser degree pRNFL thinning have shown marked associations with both level of disability and clinical progression of MS, as well as brain atrophy.…”
Section: Discussionmentioning
confidence: 99%